De novo Sequencing of the Leaf Transcriptome Reveals Complex Light-Responsive Regulatory Networks in Camellia sinensis cv. Baijiguan - Wu, Quanjin; Chen, Zhidan; Sun, Weijiang; Deng, Tingting; Chen, Mingjie (Frontiers in Plant Science, 2016)
Tea plants (Camellia sinensis L.) possess high genetic diversity that is important for breeding. One cultivar, Baijiguan, exhibits a yellow leaf phenotype, reduced chlorophyll (Chl) content, and aberrant chloroplast structures under high light intensity. In contrast, under low light intensity, the flush shoot from Baijiguan becomes green, the Chl content increases significantly, and the chloroplasts exhibit normal structures. To understand the underlying molecular mechanisms for these observations, we performed de novo transcriptome sequencing and digital gene expression (DGE) profiling using Illumina sequencing technology. De novo transcriptome assembly identified 88,788 unigenes, including 1652 transcription factors from 25 families. In total, 1993 and 2576 differentially expressed genes (DEGs) were identified in Baijiguan plants treated with 3 and 6 days of shade, respectively. Gene Ontology (GO) and pathway enrichment analyses indicated that the DEGs are predominantly involved in the ROS scavenging system, chloroplast development, photosynthetic pigment synthesis, secondary metabolism, and circadian systems. The light-responsive gene POR (protochlorophyllide oxidoreductase) and transcription factor HY5 were identified. Quantitative real-time PCR (qRT-PCR) analysis of 20 selected DEGs confirmed the RNA-sequencing (RNA-Seq) results. Overall, these findings suggest that high light intensity inhibits the expression of photosystem II 10-kDa protein (PsbR) in Baijiguan, thus affecting PSII stability, chloroplast development and chlorophyll biosynthesis.